Health Belief Model-Based Intervention for Stunting Prevention Among Toddlers in the Sikumana Health Centre Area Kupang City - Poy, Galfari Elsatria Digiferen; Lerik, M. Dinah Charlota.; Roga, Anderias Umbu; Nayoan, Christina; Marni, Marni (Pergizi Pangan DPD NTT, 2025)
Background: Stunting is a chronic nutritional issue that hinders child growth due to prolonged malnutrition from pregnancy to early childhood, with visible effects after age two. It affects cognitive and physical development, lowering the quality of future generations. Objective: This study aims to analyze the relationship between Health Belief Model (HBM) components, perceived vulnerability, severity, benefits, barriers, and cues to action and stunting prevention efforts among mothers of toddlers in the Sikumana Health Center area, Kupang City. Methods: A quantitative cross-sectional study was conducted from February 6–29, 2024, involving 89 mothers selected through sequential sampling. Data were collected using a questionnaire and analyzed with the chi-square test (p < 0.05). Results: All HBM variables showed significant associations with stunting prevention efforts: perceived vulnerability (p = 0.016), severity (p = 0.010), benefits (p = 0.044), barriers (p = 0.038), and cues to action (p = 0.000). Maternal beliefs regarding stunting risk, its consequences, benefits of action, and external motivators play a crucial role in influencing preventive behavior. Conclusion: HBM components significantly influence maternal efforts in preventing stunting. The model is effective for designing public health interventions, particularly nutrition education strategies aimed at increasing awareness and proactive maternal behavior.